Langosh, Peppi & Yeva : hot to trot - Post, Veronica, 1984- (Conundrum Press, 2023)
"As Langosh and Yeva embark on an epic cross-country journey, they discover that old wounds--and differing personal experiences--have begun to threaten their close-knit friendship. The landscape of America creates a constantly evolving backdrop to their emotional voyage. As they explore big cities, small towns, prairies and mountains, Langosh opens up to Yeva about his experience of police brutality, and the stark difference between how they respond to the situation leads to deep reflection on how the past informs their current choices. The more they seek to influence each other, the more obscured their path becomes. As Yeva comes to understand the unjust act of violence that changed his life forever, she struggles with how Langosh decides to respond to what happened. Have the values that he formed in response to harm become barriers to his personal growth? Is Yeva callous to the realities that he faces? Can they stay true to themselves and keep their friendship alive? Influenced by Jillian Tamaki, Kate Beaton and Guy Delisle, Veronica Post examines how we respond to structural harm, the power and limitations of personal agency and the divide between individual freedoms and collective responsibility."--Publisher.